Sensory Quality Of Candy Calamansi (Citrofortunella microcarpa) - Regina Pangerapan; Thema D.J. Tuju; Jenny E.A. Kandou (Universitas Sam Ratulangi, 2016)
ABSTRACTCalamansi (Citrofortunella microcarpa) in the Minahasa area often referred to as lemonfish, or lemon cui, this citrus fruit in one year can be 4 times the harvest season with thefruit of 40-42 kilograms. One Calamansi citrus fruit has 12 calories composition, with abit of fat, 1.2 grams fiber, 37 milligrams of potassium, 7.3 milligrams of vitamin C,vitamin A 54.4 milligrams, 8.4 milligrams of calcium, and water 15.5. This research willexplain the use of Calamansi that it can be processed into confectionery products.This study aimed to evaluate the panelist preference level of the color, aroma, taste andtexture of candy Calamansi and test the chemical quality candies include moisturecontent, ash content, reducing sugar and total acid. This study uses a completelyrandomized design (CRD) with 4 treatments A (80% Sucrose: 20% Glucose), B (70%Sucrose: 30% Glucose), C (60% Sucrose 40% Glucose), D (50% sucrose: 50% Glucose).All the above treatments be tested by 25 panelist. All treatment most preferred analyzedthe chemical quality of water content, ash content, reducing sugar, total acid. The resultsshowed that the candy most preferred is the treatment C with 60% sucrose and 40%glucose, with a bright yellow color, aroma and citrus flavor and texture rather hardKalamansi. While the analysis of the chemical quality of sweets Calamansi mostpreferably has a moisture content of 1.80%, ash content of 0.15%, 68.03% reducing sugarand total acid 2.28%